2021
DOI: 10.12998/wjcc.v9.i22.6418
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory myofibroblastic tumor of the pancreatic neck: A case report and review of literature

Abstract: BACKGROUND Pancreatic inflammatory myofibroblastic tumor (IMT) is a relatively rare disease that is often confused with pancreatic cancer or pancreatic neuroendocrine tumors. The histological features of IMTs show that tissue from this type of tumor contains an intermingling of fibroblast and myofibroblast proliferation, accompanied by a varying degree of inflammatory cell infiltration. CASE SUMMARY The management of an IMT occurring at the neck of the pancreas is prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 40 publications
(23 reference statements)
0
10
0
Order By: Relevance
“…Inflammatory myofibroblastic tumors (IMT) are rare mesenchymal tumors of unknown origin most commonly occurring in the lungs of children and adolescents (186). However, they have also been described in the head/neck, liver, pancreas, thyroid, and genitourinary tract (187-191).…”
Section: Inflammatory Myofibroblastic Tumormentioning
confidence: 99%
See 2 more Smart Citations
“…Inflammatory myofibroblastic tumors (IMT) are rare mesenchymal tumors of unknown origin most commonly occurring in the lungs of children and adolescents (186). However, they have also been described in the head/neck, liver, pancreas, thyroid, and genitourinary tract (187-191).…”
Section: Inflammatory Myofibroblastic Tumormentioning
confidence: 99%
“…Clinical symptoms are frequently non-specific, though obstructive jaundice may occur in the setting of a pancreatic head lesion (186). Spontaneous splenic rupture has also been reported secondary to the obstruction and congestion of splenic vessels by a pancreatic tail IMT (195).…”
Section: Inflammatory Myofibroblastic Tumormentioning
confidence: 99%
See 1 more Smart Citation
“…It has been revealed that IMT may have gene rearrangement with anaplastic lymphoma kinase (ALK)[ 3 ], and ALK positivity was also associated with a higher recurrence and less chance of distant metastasis[ 4 ]. A recent literature review by Chen et al [ 5 ] in 2021, included 30 patients with IMT occurring in the pancreas. The reported mean age of the patients was 40 years (range, 0-82 years) with an obvious male preponderance.…”
Section: Discussionmentioning
confidence: 99%
“…In this series, abdominal pain was the most frequent symptom followed by jaundice. Only five cases of asymptomatic pancreatic IMT have been reported in the medical literature[ 5 - 9 ]. Our patient had no clinical symptoms and the pancreatic mass was found on physical examination.…”
Section: Discussionmentioning
confidence: 99%